EFEKTIVITAS WHATSAPP SEBAGAI MEDIA PENGENTASAN MASALAH BELAJAR DARING - Wahyudi; Nurodin (CONS-IEDU, 2021)
Online learning at primary schools using WhatsApp media a lot. It is important to explore how effective online learning is through WhatsApp. Researchers conducted field research with descriptive qualitative approaches in various elementary schools. The results show that online learning through WhatsApp in elementary schools tends to be ineffective. It is very necessary to evaluate the role of the teacher as well as parents in this matter going forward